(3GdaJGhi GdbGOQjIs ((3eMeO GdCejf Hf CMeO Hf MSjf s)
(3ChdgG (B:s
(3cJGH GdWgGQI (B: (3GdeGA GdPi jJhVC Hg KdGKI s
(3BNQgG (B:s
(3hai GdPNjQI EHQGA GdhVi Yf GdOjf hEf hLH HYbO , UM YfOgeG hVef , hdG jUM YfO GdKGfi hEf hLH GfJgi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQCgG hUMMgG eMeO Hf eMeO HjQe SfI (B1220(3g` HChdgG Jedc HGSe eMeO Hf MSjf HjQe hMajOg eMeOs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdESdGejs